(untitled) (International Seven Journal of Health Research, 2023)
Sepsis is defined as an organic dysfunction resulting from a deregulated immune system response to an infectious process. It is characterized as a public health problem, has a high lethality rate and a high incidence in Intensive Care Units. The aim of this study was to describe the main preventive measures and treatment that are part of nursing care in cases of sepsis in the ICU. This is a descriptive bibliographic study carried out in 2020 in the Scientific Electronic Library Online (Scielo), Google Scholar and Virtual Health Library databases. We used 12 articles from 2014 to 2019 that met the inclusion criteria and objectives of the study. It was found that most of the studies highlighted the need for more effective treatment and care; however, little was said about the specific procedures to be implemented by nursing professionals. Based on the results obtained, it can be inferred that there is a need for more technical scientific knowledge on the part of the nursing team, which highlights the need for training and continuing education activities in the sectors.